Clicks to Cravings: The Role of E-Commerce Design and Sales Promotion in Buying Behavior on Shopee - Daisy Mui Hung Kee; Anis Natasya; Hui San Ang; Jia Qian Ang; Angeline An Qi Tan (Asia Pacific Journal of Management and Education (APJME), 2026)
Shopee is the most visited e-commerce and retail platform in Malaysia, and a leading site across Southeast Asia, making it a suitable context for exploring online buying behavior. This study examines how sales promotion, perceived convenience, perceived ease of use, and perceived usefulness affect customer satisfaction and buying behavior. Data were obtained from 200 active Shopee users via an online questionnaire using a five-point Likert scale. Results indicate that sales promotion significantly impacts both customer satisfaction and buying behavior and is the only factor directly driving purchases. Perceived convenience and perceived usefulness improve customer satisfaction but do not directly affect buying behavior, while perceived ease of use has no significant effect. Our results contribute to research on consumer behavior in e-commerce and offer practical insights for online retailers to increase engagement and sales through effective digital design and promotion.